Večkulturnost in diskriminacija v evropskem kulturnem okolju in medijskih diskurzih - Medica, Karmen (Monitor ISH, 2006)
The practices of individual European countries suggest that a society must know how to be discriminating without being discriminatory. A discriminating society is committed to the full recognition of legitimate and relevant differences, which is a prerequisite for the development of tolerance. Such a society perceives social diversity as a multi-directional, connecting, and relational phenomenon. In a discriminatory society, by contrast, social and cultural diversity is marginalised and ignored. Nowadays, the competence to mould a society which would be open to cultural diversity in all processes of social communication rests with the media.
Keywords: etničnost; human migration; migracije; manjšine; večkulturnost; diskriminativnost; diskriminatornost